SOSIALISASI RANCANGANRUMAH TANGGAP BENCANA GEMPA - Sidiq Tono (Asian Journal of Innovation and Entrepreneurship, 2014)
Indonesia is a country that has many volcanoes. A large number of volcanoes lead to potential disaster due to the impact of large volcanic eruption. One is a volcanic earthquake which occurred when volcanoes will erupt. Volcanic earthquakes occur due to volcanic activities. Earthquakes caused by the movement of magma inside the volcano. As a result of the earthquake from vibrating homes to vibrate, crack until the collapse. One of volcanic earthquakes that occurred is of volcanic earthquakes at the merapi mountain on the island of Java. Earthquake felt by the residents of villages around the merapi mountain. One village is fairly close to the merapi mountain is dukuh Pencil, Munggung village, Karangdowo district, Klaten, Central Java. So the village has the potential to feel the impact of the earthquake merapi mountain. To reduce the impact of the earthquake is carried socialization of how to design a home that houses the earthquake disaster response that were built by residents of the  dukuh Pencil, Munggung  village can survived and did not collapse when the earthquake occurred